Effects of Thermal Conditioning on Changes in Hepatic and Muscular Tissue Associated With Reduced Heat Production and Body Temperature in Young Chickens - Ouchi, Yoshimitsu; Chowdhury, Vishwajit S.; Cockrem, John F.; Bungo, Takashi (Frontiers in Veterinary Science, 2021)
Effects of increased summer temperatures on poultry production are becoming more pronounced due to global warming, so it is important to consider approaches that might reduce heat stress in chickens. Thermal conditioning in chickens in the neonatal period can improve thermotolerance and reduce body temperature increases when birds are exposed to high ambient temperature later in life. The objective of this study was to investigate physiological and molecular changes associated with heat production and hence body temperature regulation under high ambient temperatures in thermally conditioned chicks. Three-day-old broiler chicks (Chunky) were thermally conditioned by exposure to a high ambient temperature (40°C) for 12 h while control chicks were kept at 30°C. Four days after the treatment, both groups were exposed to 40°C for 15 or 90 min. The increase in rectal temperature during 90 min of exposure to a high ambient temperature was less in thermally conditioned than control chicks. At 15-min of re-exposure treatment, gene expression for uncoupling protein and carnitine palmitoyletransferase 1, key molecules in thermogenesis and fatty acid oxidation, were significantly higher in pectoral muscle of control chicks but not conditioned chicks. Hepatic argininosuccinate synthase (ASS) decreased and hepatic argininosuccinate lyase (ASL) increased after reexposure to a high temperature. The concentrations of hepatic arginosuccinic acid, and ASS and ASL expression, were upregulated in conditioned chicks compared with the control chicks, indicating activity of the urea cycle could be enhanced to trap more energy to reduce heat production in conditioned chicks. These results suggest thermal conditioning can reduce the increase in heat production in muscles of chickens that occurs in high ambient temperatures to promote sensible heat loss. Conditioning may also promote energy trapping process in the liver by altering the heat production system, resulting in an alleviation of the excessive rise of body temperature.